Structural correlation of creative thinking skills, problem-solving, and entrepreneurial self-efficacy in biology education students: PLS SEM analysis - Ika Wardani; Murni Sapta Sari; S. Sulisetijono; Abdul Gofur; Zainuddin bin Hassan; M. Arsyad (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Entrepreneurship project-based learning model on the problem-solving skills of Biology Education study. This study aims to describe the structural correlation construction of creative thinking skills, problem-solving skills, and entrepreneurial self-efficacy among biology education students in East Java. The population in this study was undergraduate (S1) Biology Education students from universities in East Java, Indonesia. The research sample comprises 405 students from these institutions who have undergone learning related to plant materials for at least one semester. The instruments used in this research were test instruments and questionnaires. The essay test for assessing creative thinking skills draws upon six indicators adapted from Greenstein. essay test instrument used for collecting data on problem-solving skills was developed based on six indicators adapted from Mourtos et al. The data collection instrument for entrepreneurial self-efficacy relied on a questionnaire developed by Gedeon & Valliere. Data analysis technique employed was Structural Equation Modeling (SEM) with the SmartPLS application. The results of the study indicate a significant correlation of creative thinking, problem-solving skills, and entrepreneurial self-efficacy in biology education students in East Java. There is a significant effect of creative thinking skills on entrepreneurial self-efficacy, creative thinking skills on problem-solving skills, and problem-solving skills on entrepreneurial self-efficacy.